2007
DOI: 10.1007/s11095-007-9508-9
|View full text |Cite
|
Sign up to set email alerts
|

Proangiogenic Potential of a Collagen/Bioactive Glass Substrate

Abstract: These studies suggest that this bioactive glass possesses a robust proangiogenic potential, and this strategy may provide an alternative to recombinant inductive growth factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
159
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(174 citation statements)
references
References 42 publications
11
159
2
2
Order By: Relevance
“…For example, it has been demonstrated that dissolution products from bioactive glasses up-regulate the expression of genes that control osteogenesis [7,51], which explains the higher rate of bone formation in comparison to other inorganic ceramics such as hydroxyapatite [52]. Further studies using 45S5 Bioglass ® particles have shown encouraging results regarding potential angiogenic effects of Bioglass ® , i.e., increased secretion of vascular endothelial growth factor (VEGF) and VEGF gene expression in vitro, as well as enhancement of vascularization in vivo [53][54][55][56] (see §4). In addition, the incorporation of particular ions into the silicate network, such as silver [20][21][22] and boron [26,27], has been investigated in order 6 to develop antibacterial and antimicrobial materials.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been demonstrated that dissolution products from bioactive glasses up-regulate the expression of genes that control osteogenesis [7,51], which explains the higher rate of bone formation in comparison to other inorganic ceramics such as hydroxyapatite [52]. Further studies using 45S5 Bioglass ® particles have shown encouraging results regarding potential angiogenic effects of Bioglass ® , i.e., increased secretion of vascular endothelial growth factor (VEGF) and VEGF gene expression in vitro, as well as enhancement of vascularization in vivo [53][54][55][56] (see §4). In addition, the incorporation of particular ions into the silicate network, such as silver [20][21][22] and boron [26,27], has been investigated in order 6 to develop antibacterial and antimicrobial materials.…”
Section: Figurementioning
confidence: 99%
“…After two weeks of implantation, histological analyses of calvaria demonstrated significantly greater neo-vascularisation and vascular density within defects treated with 45S5 BG (35 ± 16 vessels/mm 2 ) than with collagen controls alone (12 ± 2 vessels/mm 2 ) ( Figure 17). The angiogenic effect of bioactive glass was, however, much more pronounced in bioactive glass-based scaffolds (i.e., loaded sponges [56], discs [208], meshes [203], tubes [209] and porous glass-ceramics scaffolds [52,121,122]) than in composite structures incorporating and fully embedding bioactive glass particles (e.g., microsphere composites [164], or foams [55,210]). However, in vivo results so far are inconsistent with in vitro results, and provide an incomplete picture concerning the suggested angiogenic potential.…”
Section: Effect Of Bioactive Glass On Angiogenesismentioning
confidence: 99%
“…For a plain biofunctionalization of the scaffold materials, we referred to a previously published technique, 32 where cell adhesion on the polypropylene meshes could be clearly enhanced by coating them before seeding with collagen containing extracellular matrix-like coating. Leu and Leach, 13 as well as Yao et al 37 already showed that collagen does not produce false-positive angiogenic side effects: Sponges made of collagen type-1 improved neither endothelial cell proliferation, HUVEC tube formation or an upregulation of VEGF production in coculture experiments in vitro 13 nor an ingrowth of blood vessels in the CAM angiogenesis assay in vivo.…”
mentioning
confidence: 99%
“…[6][7][8][9] More recently, studies have shown that bioactive glasses may also be effective in promoting the vascularization of tissue constructs in different combinations, for example, as sintered scaffolds and composites. [10][11][12][13][14][15][16][17] The use of Bioglass Ò to fabricate scaffolds using a foam replica method was introduced in 2006 followed by studies on the possible angiogenic effect of such scaffolds. 18 Similar bioactive glass scaffolds were investigated in coculture studies using human umbilical vein endothelial cells (HUVEC) and human osteoblasts, 14 and it was shown that the scaffolds were able to support both endothelial and human osteoblast proliferation.…”
mentioning
confidence: 99%
“…As is well known, they can bond to both bone and soft tissue, and the extent of the bioactivity can be controlled through adjusting the composition. They have recently been found to show proangiogenic tendencies [24][25][26][27][28], further promoting their use in tissue engineering. They are also resorbable, because the glass structure is fragmented and gradually dissolves during the process of forming an amorphous calcium phosphate layer and afterwards.…”
Section: Bioactive Glassesmentioning
confidence: 99%